An evaluation on the effect of fabric softener on the wrinkle recovery and hand of natural and manufactured fabrics - Vinluan, Agnes De Mesa
For the past years since fabric softener had been introduced to the Philippine market, it has become a part of the Filipino household. Laundering has been changed with the introduction of fabric softener as it promised to leave a lasting scent and soften clothes. In this light, the study focused on the effect of fabric softener to the wrinkle recovery and hand of on fabrics made from natural and manufactured fibers. Linen was chosen to represent the natural fiber group because of its poor resiliency while polyester was chosen from manufactured fiber group since it was the most used fiber. To identify the fabric softener brand to be used in the experiment, a brand survey was conducted, and Downy has been identified as the most popular brand. The Wrinkle Recovery Test for Appearance was used as the data gathering tool to study the effect of fabric softener on the wrinkle recovery of linen and polyester. The experiment result showed that fabric softener only improved the polyester. To study the improvement on the hand of the fabrics, a survey that would identify the perceived hand of the fabrics was administered. Survey results proved that hand was improved with the use of fabric softener on both linen and polyester. For the Wrinkle Recovery Test and survey of perceived hand, increasing the mount of fabric softener had not resulted to an dramatic improvement. Therefore the researcher, after this study, recommends using fabric softener according to the instructions of the fabric softener manufacturer.